Tribes and tribulations: interdisciplinary eHealth in providing services for people with a traumatic brain injury (TBI) - M. Hines; M. Brunner; S. Poon; M. Lam; V. Tran; D. Yu; L. Togher; T. Shaw; E. Power (BMC, 2017)
Abstract Background eHealth has potential for supporting interdisciplinary care in contemporary traumatic brain injury (TBI) rehabilitation practice, yet little is known about whether this potential is being realised, or what needs to be done to further support its implementation. The purpose of this study was to explore health professionals' experiences of, and attitudes towards eHealth technologies to support interdisciplinary practice within rehabilitation for people after TBI. Methods A qualitative study using narrative analysis was conducted. One individual interview and three focus groups were conducted with health professionals (n = 17) working in TBI rehabilitation in public and private healthcare settings across regional and metropolitan New South Wales, Australia. Results Narrative analysis revealed that participants held largely favourable views about eHealth and its potential to support interdisciplinary practice in TBI rehabilitation. However, participants encountered various issues related to (a) the design of, and access to electronic medical records, (b) technology, (c) eHealth implementation, and (d) information and communication technology processes that disconnected them from the work they needed to accomplish. In response, health professionals attempted to make the most of unsatisfactory eHealth systems and processes, but were still mostly unsuccessful in optimising the quality, efficiency, and client-centredness of their work. Conclusions Attention to sources of disconnection experienced by health professionals, specifically design of, and access to electronic health records, eHealth resourcing, and policies and procedures related to eHealth and interdisciplinary practice are required if the potential of eHealth for supporting interdisciplinary practice is to be realised.